Characterizing structure of cross-disciplinary impact of global disciplines: A perspective of the Hierarchy of Science - Liu Ruolan; Mao Jin; Li Gang; Cao Yujie (Journal of Data and Information Science, 2024)
Interdisciplinary fields have become the driving force of modern science and a significant source of scientific innovation. However, there is still a paucity of analysis about the essential characteristics of disciplines’ cross-disciplinary impact.